2005
DOI: 10.2174/1568007053544138
|View full text |Cite
|
Sign up to set email alerts
|

Poly (ADP-Ribose) Polymerase Inhibitors as Potential Therapeutic Agents in Stroke and Neurotrauma

Abstract: Poly (ADP-ribose) polymerase-1 (PARP-1) is a DNA-binding protein that is primarily activated by nicks in the DNA molecule. It regulates the activity of various enzymes - including itself- that are involved in the control of DNA metabolism. Upon binding to DNA breaks, activated PARP cleaves NAD+ into nicotinamide and ADP-ribose and polymerizes the latter on nuclear acceptor proteins including histones, transcription factors and PARP itself. Poly(ADP-ribosylation) contributes to DNA repair and to the maintenance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 160 publications
(233 reference statements)
1
29
0
1
Order By: Relevance
“…The mechanisms account for the neurocytotoxicity elicited by peroxynitrite are multiple, among them, induction of DNA strand breaks and the subsequent activation of poly (ADP-ribose) polymerase have been demonstrated to be critical events [11]. In this context, DNA single-stranded breakage initially trigged by endogenous or exogenous peroxynitrite may lead to cell death [12]. Moreover, studies have also demonstrated that some peroxynitrite-scavenging compounds are able to protect against peroxynitrite-mediated DNA strand breaks in target cells [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms account for the neurocytotoxicity elicited by peroxynitrite are multiple, among them, induction of DNA strand breaks and the subsequent activation of poly (ADP-ribose) polymerase have been demonstrated to be critical events [11]. In this context, DNA single-stranded breakage initially trigged by endogenous or exogenous peroxynitrite may lead to cell death [12]. Moreover, studies have also demonstrated that some peroxynitrite-scavenging compounds are able to protect against peroxynitrite-mediated DNA strand breaks in target cells [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Although the antioxidant properties of EP appear to be responsible, at least partially, for its neuroprotective effects, it remains unclear whether the neuroprotective effects of EP may also occur through other mechanisms. Since peroxynitrite is involved in the pathogenesis of neurodegenerative diseases, and induction of DNA strand breaks is a critical initial lesion leading to cell death induced by peroxynitrite [11,12,22], in this study using uX-174 plasmid DNA as an in vitro system, we have investigated the effects of EP on peroxynitrite-induced DNA strand breaks. Our results demonstrate for the first time that EP at physiologically relevant concentrations inhibits peroxynitrite-mediated DNA strand breakage and hydroxyl radical formation in a concentration-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…In the cytoplasm, the process of AIF movement to the nucleus depends on its nuclear localization signal where it induces large-scale DNA fragmentation (10,13). The two death pathways that depend on PARP1 have been demonstrated in animal models of brain ischemia, myocardial injury, Parkinson's disease, and diabetes (14)(15)(16). Thus, because of its involvement in important biological processes, PAR metabolism is tightly controlled both spatially and temporally.…”
mentioning
confidence: 99%
“…PARP-1 is involved in various cellular processes such as gene expression, amplification, malignant transformation, differentiation, division, DNA replication, mitochondrial function, DNA repair, chromatin replication, transcriptional regulation, cell death, and inflammatory response [16,17]. The human PARP-1 gene includes 23 exons spanning 43 kb and is located in 1q41-q43.…”
Section: Parp-1mentioning
confidence: 99%